2022
DOI: 10.37992/2022.1303.146
|View full text |Cite
|
Sign up to set email alerts
|

TRY 4: A high yielding, mid early sodicity tolerant rice variety suited to Tamil Nadu

Abstract: Sodicity tolerant rice culture TR 05031, a derivative of the cross ADT 39 x CO 45 was released as Rice TRY 4 during the year 2021 as a mid early duration variety with 127 days duration with high yield, high milling (68.1 %) and head rice recovery (57.2 %). Twelve years of testing across 181 locations in Tamil Nadu revealed that the culture is high yielding (5730 kg/ha with 22.00 per cent increased grain yield over TKM 13 and 16.50 per cent over ADT 39) in salt affected soils. EDAX under SEM studies confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…It is in agreement with the studies of Tripathi et al (2018). In case of different rice variety, the highest CAT activity was recorded in CO 43 followed by TRY 3, TRY 1, CSR 27, TRY 2 and the lowest activity was found in W P. The results are in accordance with Geetha et al (2022), where the tolerant rice varieties recorded higher CAT activity than susceptible varieties. In interaction between the ESP levels and variety, the tolerant 6, 11.5, 11.9, 11.7, 11.5 and 11.1 min -1 g -1 , respectively (Table 5).…”
Section: Catalase Activitysupporting
confidence: 90%
“…It is in agreement with the studies of Tripathi et al (2018). In case of different rice variety, the highest CAT activity was recorded in CO 43 followed by TRY 3, TRY 1, CSR 27, TRY 2 and the lowest activity was found in W P. The results are in accordance with Geetha et al (2022), where the tolerant rice varieties recorded higher CAT activity than susceptible varieties. In interaction between the ESP levels and variety, the tolerant 6, 11.5, 11.9, 11.7, 11.5 and 11.1 min -1 g -1 , respectively (Table 5).…”
Section: Catalase Activitysupporting
confidence: 90%
“…This may be due to several anatomical and physiological mechanisms of these genotypes facilitating them to outperform the check genotypes under sodicity. Geetha et al (2022) These genotypes were also evaluated for sodicity tolerance under hydroponics condition. The susceptibility reaction of all these outperforming genotypes showed that they are susceptible to sodicity stress at seedling stage (Unpublished).…”
Section: Resultsmentioning
confidence: 99%